Illness, Healthcare, and Health Insurance: Socio-economic Perspective in Nepalese Context - Acharya, Devaraj; Wagle, Bishnu Prasad; Bhattarai, Radha (Nepalese Journal of Insurance and Social Security, 2019)
The Government of Nepal has introduced a health insurance programme since 2016. The main essence of the program is to reduce the gap in the utilization of health services between poor and rich, to reduce the out-of pocket expenditure while receiving the healthcare services, and to protect the family from poverty due to catastrophic healthcare expenditure. Researchers review the policy, programme and existing practice Data from Health Insurance Board shows that the programme appears not so effective in many districts but it looks successful in some districts where private healthcare providers are existing as a referral hospital. It is still unanswered whether the HIP is going to boost industrialists in the name of basic rights, health equity and social justice. The paper studies socio-economic and political perspectives of healthcare and health insurance with reference to Nepal and concludes that the healthcare system needs to reform for real welfare, social justice, and citizens' access and right to healthcare.